Ensuring Sustainable Urban Transformation in Indonesia: Toward Indonesia Emas 2045 - B. Setiawan; Tri Mulyani Sunarharum (Pusbindiklatren Bappenas, 2020)
Of the many important events that occurred in the two decades of the 21st century, the process of accelerating urbanization—especially in third-world countries—became something quite phenomenal. It's never even happened before. In the early 2000s, only about 45 percent of the population in the third world lived in urban areas, by 2020 the number had reached about 55 percent. Between now and 2035 the percentage of the population living in urban areas will reach about 85 percent in developed countries. Meanwhile, in developing countries will reach about 65 percent. By 2035, it is also projected that about 80 percent of the world's urban population will live in developing countries' cities.